‘A veritable Dickens shrine’: Commemorating Charles Dickens at the Dickens House Museum - Catherine Malcolmson (19, 2011)
In 1925, the Dickens Fellowship founded the ‘Dickens House Museum’ at Number 48 Doughty Street, London. The site held a particular significance for Fellowship members as it was the last remaining London home of the author and the location was valued for its personal association with Dickens, establishing a sense of ‘familial intimacy’ with the author. The museum was conceived both as a place of access to Dickens and as a receptacle for the display of objects associated with him. Promotional material utilized a language of feeling, in which the museum’s founders stated their intention that the Museum would become ‘a veritable Dickens shrine, inspiring sentiment and inculcating a spirit of veneration for the great writer’. The items displayed were designed to produce an emotional response in the museum’s visitors and to serve as an act of commemoration to Dickens. This paper will explore both the extraordinary devotion which Dickens inspired and the forms by which he was memorialised and commemorated. It will evaluate the items chosen for display, from a replica of the Dingley Dell kitchen from The Pickwick Papers (1836–37), to the various ‘Dickens relics’ which were collected, and the responses which they produced in early visitors. It will demonstrate that through their activities, writings, and establishment of the Dickens Museum, the Dickens Fellowship presented a particular version of Dickens’s legacy to the public: a nuanced and sentimental portrait of the author which remains in the popular imagination today.